The first 40-days experience and clinical outcomes in the management of coronavirus covid-19 crisis. Single center preliminary study. - Allawi, Jaffar S; Abbas, Hassan M; Rasheed, Jawad I; Sulaiman, Tharwat I.; Gatea, Ali A; Al-Lami, Faris; Al-Diwan, Jawad K; Al-jabory, Adnan M; Waheeb, Muhammed; Abdurudha, Yasir I; Al-Kaabi, Laith S; Al-Shuwaili, Saeb J; et al. (Journal of the Faculty of Medicine Baghdad, 2020)
Background: The World Health Organization (WHO) has announced that coronavirus covid-19 is a pandemic. The first case of covid-19 was confirmed in Iraq on the 24th of February 2020, which was of an international student who travelled recently to Iraq. This review is the universal data analysis of the first 40-days of coronavirus covid-19 patients admitted to Medical City Teaching Hospital (MCTH) including their clinical outcome. Objective: We have conducted this study to describe the first 40-days experience in management of corona virus covid-19 and the clinical outcomes of patients treated with a protocol adopted in the first of March 2020 (described in the attachment). Patients and methods: This is a preliminary descriptive study demonstrating all actions conducted in MCTH to manage coronavirus patients. The study included 79 patients who were RT-PCR positive out of 469 suspects who were screened in the outpatient clinic of MCTH according to WHO criteria. The clinical outcomes were defined as complete clinical and immuno-virologic recovery, non-recovery and death. Complete recovery was defined as negative RT-PCR conducted twice after disappearance of clinical symptoms. Death was subclassified as death within 24 hours and after 24 hours in the hospital or intensive care unit. Non-recovered cases were defined as persistent symptoms or persistent positive RT-PCR after disappearance of clinical symptoms. The treatment protocol was Oseltamivir 75 mg BID for 5 days with Hydroxychloroquine (400mg BID first day then 200mg BID for 5 days) for moderate cases, adding Kaletra (Lopinavir-Ritonavir (200/ 50 mg) 2 tablets PO BID 5 days for severe cases, and ribavirin for critical cases. Results. The total no of symptomatic patients and PCR positive was 79 patients out of 469 screened suspects (16.84%). The mean age was (47.18 -/+ 18). they are prevalent among the age group (40-50 years). There were 59 male patients (74.68%) in comparison to 20 female patients (25.31%). There were 13(16.45%) patients with moderate disease ,15(18.98%) patients with severe disease, and 13(16.45%) patients with very severe disease required admission to critical care. The clinical recovery (free of clinical symptoms) was seen in 84.9 %. Complete recovery was seen in 41 (51.89%) patients. Death within 24 hours was seen in 6 patients (7.5%) while confirmed death after 24 hours was seen in 4 (5%). Conclusions: The treatment protocol is well conducted in this center with promising rate of complete recovery and excellent rate of clinical recovery. The high initial death rate was compensated after three weeks as more orientation of medical staff and peoples about the disease.